Refining ESG Disclosure's Role in Corporate Economic, Environmental, and Social Sustainability Performance - Ray, Samrat; Hardi, Irsan (Heca Sentra Analitika, 2024)
This research examines the complexities of corporate sustainability, exploring the interconnections between environmental, social, and governance (ESG) disclosure, corporate governance frameworks, investor engagement in ESG practices, and sustainability performance improvements. Regression analysis were employed to analyze data collected from 121 participants across various professions in India. The findings indicate that ESG disclosures have an impact on the Sustainability Performance Transformation Index (SPTI), suggesting that disclosures alone may not necessarily lead to improved sustainability. Additionally, SPTI was found to be correlated with company management practices and investor engagement in ESG issues. The model demonstrates strong explanatory power (R2 = 0.979), underscoring the importance of adopting multidisciplinary methodologies for achieving lasting transformation. The conclusions drawn from this study offer insights that businesses, investors, and policymakers can leverage to strike a balance between long-term sustainability objectives and economic development.